Nickel-Catalyzed Cross-Coupling of Chromene Acetals and Boronic Acids - Graham, Thomas J. A. (Org Lett, 2012)
A modular and highly efficient protocol for the synthesis of 2-aryl- and heteroaryl-2H-chromenes is described. Under base-free conditions, readily accessible 2-ethoxy-2H-chromenes undergo C(sp(3))–O activation and C(sp(3))–C bond formation in the presence of an inexpensive nickel catalyst and boronic acids. This new strategy enables broad access to 2-substituted-2H-chromenes and has been applied to the late-stage incorporation of complex molecules, including the pharmaceuticals loratidine and indomethacin methyl ester.